Autoimmune Retinopathy in a Patient with Autoimmune Polyendocrine Syndrome Type I. (1st April 2013) - Breunig, Adam; Lee, Michael S.; Miller, Bradley S.; Binstadt, Bryce A.; Anderson, Mark S.; Montezuma, Sandra
Abstract: Purpose : To present a case of autoimmune retinopathy resulting from a mutation in the autoimmune regulator (AIRE) gene. Design : Case Study Methods : Case Review Results : Mild improvement of goldmann visual field following treatment with systemic and local immunosuppression. Conclusions : There are a limited number of cases linking autoimmune retinopathy with a mutation in the AIRE gene. Further research is needed to find more effective treatment and to prevent tissue damage.